The Impact of Process Variables on the Quantity and Quality of Biogas Generated from Anaerobic Digestion of Food Waste and Rumen Contents - Amoo, Afeez Oladeji; Ahmed, Sabo; Haruna, Adamu (Tecno Scientifica Publishing, 2023)
This research aimed to investigate how combining process variables affects biogas production from anaerobic digestion of food waste and rumen contents. A mixture design was used to evaluate the effects of temperature, pH, agitation frequency, and retention time on biogas quantity and quality. Anaerobic mono-digestion and co-digestion were performed using 2 liter single-stage plastic anaerobic digesters. Cumulative biogas volume and its composition, including carbon dioxide, hydrogen sulphide, moisture, and methane content, were estimated volumetrically. The highest biogas volume and quality were obtained under the following conditions: food waste (0.30 kg), rumen content (0.30 kg), water content (0.40 kg), temperature (34.0° C), pH (9.0), agitation frequency (4 times/day), and retention time (32 days). Combining process variables can significantly impact biogas quantity and quality, and optimal process parameters vary depending on the substrate and operational conditions. Anaerobic digestion can effectively manage organic waste, produce renewable energy, and mitigate greenhouse gases.